Peran Penting Kemampuan Komunikasi Yang Baik Untuk Meningkatkan Kualitas Sumber Daya Manusia / Anggota Dharma Wanita Di Dharma Wanita Persatuan Dinas Pertanian Dan Ketahanan Pangan Kabupaten Banyumas - Poppy Fitrijanti Soeparan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Communication is very important thing in the life of humans. In society, individuals are required to be able to communicate well with each other. Communication is intended so that all messages and conversations within the organization can be understood by leaders and members of the organization. Communication in the Dharma Wanita organization between leaders, administrators still needs to be improved. Therefore good communication skills must be honed and added. It is all because the quality of good human resources depends on the ability to communicate. Activities at Dharma Wanita such as regular Dharma Wanita coordination meetings, trainings, counsellings, routine internal meetings of DWP Dinpertan KP have increased knowledge and understanding in communication, both held face to face and in social media groups. This increase in ability is correlated with an increase in the quality of human resources, in this case the Dharma Wanita members.